Pseudomembranous colitis: fatal clostridium difficile infection in pregnancy - Jenosha, I.; Selvaratnam, G.; Pradeepan, J. A.; Kumanan, T.; Pranavan, S. (Sri Lanka College of Internal Medicine, 2025)
Clostridium difficile infection (CDI) is a disease primarily affecting the large intestine, characterised by diarrhoea, abdominal pain and fever due to enterotoxins. The severe form of this infection, known as pseudomembranous colitis, carries a high mortality rate if not promptly recognised and treated. Its incidence is on the rise among pregnant women, posing significant risks to both the mother and foetus. Here, we report a fatal case of pseudomembranous colitis in a young pregnant woman. Maintaining a high index of clinical vigilance in pregnant individuals experiencing unexplained diarrhoea enables timely investigations and prompt treatment, averting adverse maternal and foetal outcomes.
Keywords: CDI in pregnancy; Clostridium difficile; Pseudomembranous colitis; Morbidity in pregnancy